MODEL EPIDEMIK CAMPAK DENGAN ADANYA VAKSIN PADA POPULASI RENTAN DAN SUPPORT PADA POPULASI TEREKSPOSE - Tri Puspa Lestari; Yuni Yulida; Aprida Siska Lestia (LPPM Universitas Terbuka, 2023)
Measles is a highly contagious disease and often occurs in children due to malnutrition, especially children with vitamin A deficiency and a weakened immune system. In addition to vaccination, the role of parents is needed in the form of support to control the development of the virus in the body. This measles disease can be modeled through a mathematical model, especially epidemic model. This study aims to explain the formation of a mathematical model of measles, determine the equilibrium point, basic reproduction number, stability analysis, and to perform numerical simulations on the model. The research procedure begins with construct a model using a system of nonlinear differential equations. The basic reproduction number can be determined using the next generation matrix method and analysis of model stability using the linearization method. While numerical simulation has been carried out using the fourth order Runge Kutta method. The result of this study is the formation of a mathematical model of measles with a population consisting of four compartments, namely Susceptible, Exposed, Infected and Recovered. Disease control is carried out in the model, namely vaccines in the Susceptible population and support measures in the Exposed population. From the model formed, two equilibrium points are obtained, namely the disease-free equilibrium point and the endemic equilibrium point. Furthermore, the basic reproduction number formula and analysis of the stability of the model at the disease-free equilibrium point and endemic equilibrium point are also obtained. Finally, a simulation model is presented to support stability analysis and comparison of solutions for the Infected population before being given control support and after being given control support with variations in vaccine percentages.